2012
DOI: 10.3354/cr01042
|View full text |Cite
|
Sign up to set email alerts
|

European drought regimes under mitigated and unmitigated climate change: application of the Community Integrated Assessment System (CIAS)

Abstract: Climate change is expected to cause significant changes in the future distribution of precipitation, as well as in the frequency and intensity of high and low rainfall events across the world. In particular, there is an expectation of drying in southern Europe and wetting in northern Europe, with some regions such as southern UK experiencing drier summers and wetter winters. In this study, a community integrated assessment system (CIAS) is used to project the impacts of climate change associated with various e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 42 publications
1
12
0
1
Order By: Relevance
“…The findings for Spain and Portugal are consistent with the consensus reached by many other modelling studies that there will be a decline in precipitation in the Mediterranean with increased drought frequency and duration (e.g. Warren et al 2012;Blenkinsop and Fowler 2007).…”
Section: Identification and Quantification Of Drought Eventssupporting
confidence: 79%
See 4 more Smart Citations
“…The findings for Spain and Portugal are consistent with the consensus reached by many other modelling studies that there will be a decline in precipitation in the Mediterranean with increased drought frequency and duration (e.g. Warren et al 2012;Blenkinsop and Fowler 2007).…”
Section: Identification and Quantification Of Drought Eventssupporting
confidence: 79%
“…As the study focuses on the first half of the 21 st century there was little variability seen between results generated using the A1FI and 450ppm scenarios. As such, the implementation of a stringent mitigation policy is projected to have limited effect on worsening drought conditions from 2003-2050 compared to the A1FI scenario, whilst it should be noted that it has been shown that mitigation would greatly reduce changes in drought regime in the second half of the 21 st century, at least in Europe (Warren et al 2012) . Instead, much of the uncertainty in future projections of drought events, including the direction of change, was linked to the GCM used, consistent with Goodess et al, (2003) who reports that for the early 21 st century inter-model variability tends to be greater than inter-scenario variability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations